Critical Breaths in Transit: A Review of Non-invasive Ventilation (NIV) for Neonatal and Pediatric Patients During Transportation - Ide, Nellie; Allen, Grace; Ashworth, Henry Charles; Dada, Sara (Frontiers in Pediatrics, 2021)
Respiratory illnesses are a leading cause of death for children worldwide, with the majority of these cases occurring from preterm birth complications or acute respiratory infections. Appropriate respiratory intervention must be provided quickly to lower the chances of death or permanent harm. As a result, respiratory support given in prehospital and interfacility transport can substantially improve health outcomes for these patients, particularly in areas where transportation time to appropriate facilities is lengthy. Existing literature supports the use of non-invasive ventilation (NIV), such as nasal or bilevel continuous positive airway pressure, as a safe form of respiratory support for children under 18 years old in certain transportation settings. This mini review summarizes the literature on pediatric NIV in transport and highlights significant gaps that future researchers should address. In particular, we identify the need to: solidify clinical guidelines for the selection of eligible pediatric patients for transport on NIV; explore the range of factors influencing successful NIV implementation during transportation; and apply appropriate best practices in low and middle income countries.